Bursting radiation growth silicon nitride nanowire modified carbon fiber material and preparation method thereof
By forming a double-layer pore structure of silicon nitride nanowires and carbon nanotube modified carbon fibers with burst radiation growth on the surface of the carbon fiber, the problem of high oxidation weight loss rate of carbon fibers at high temperatures is solved, and better oxidation resistance is achieved and Extended service life.
Patent Information
- Application Number
- CN202411469655.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2025-01-07
AI Technical Summary
The existing carbon fiber materials have a high oxidation weight loss rate at high temperatures, which affects their service life. The existing modification methods still have a high oxidation weight loss rate above 600℃.
Using burst radiation to grow silicon nitride nanowire modified carbon fiber materials, the burst radiation-growing silicon nitride nanowires are formed on the surface of the modified carbon fiber of carbon nanotubes, and a double-layer pore structure is formed to block heat transfer and oxygen contact. The iron element at the tail end of the carbon nanotube serves as the nucleation site of the silicon nitride nanowires, enhancing binding force and catalytic effect.
It significantly reduces the oxidative weight loss rate of carbon fiber materials at high temperatures, extends the use time, and improves the oxidative resistance, which is better than the oxidative weight loss rate of modified carbon fiber materials reported in the literature.
Smart Images

Figure CN119265927A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of preparation of modified carbon fiber materials, and specifically relates to a burst radiation-grown silicon nitride nanowire modified carbon fiber material and a preparation method thereof. Background Art
[0002] Carbon fiber materials have the characteristics of friction resistance, thermal conductivity, corrosion resistance, high specific strength and specific modulus. However, when the temperature is higher than 400°C, the carbon fiber begins to oxidize, and the specific strength and specific modulus of the carbon fiber material caused by oxidation decrease, which seriously affects the service life of the carbon fiber material. Therefore, it is of great significance to delay or prevent the oxidation of carbon fiber. Silicon nitride nanomaterials have excellent properties such as good chemical stability, good high temperature resistance, good flexibility, and corrosion resistance. Applying silicon nitride nanowires on the surface of carbon fiber is an effective means to delay the oxidation of carbon fiber. Different growth forms of silicon nitride nanomaterials have different pore structures, different effects on hindering heat transfer and oxygen isolation, and different antioxidant effects. Therefore, preparing silicon nitride nanostructures with special morphology on the surface of carbon fiber is of great value for improving the antioxidant capacity of carbon fiber.
[0003] Reference 1 “A method for improving the high-temperature oxidation resistance of carbon fiber” reported that carbon fiber was coated with a attapulgite coating, and the weight loss rate of the obtained modified carbon fiber material under 600°C oxidation conditions was 65%.
[0004] Reference 2 “Improvement of carbon fiber oxidation resistance by thinceramic coating using silica particles” reported the preparation of silicon nitride coating on the surface of carbon fiber. Thermogravimetric analysis results showed that the oxidation weight loss rate of the material was 40% at 600°C.
[0005] The above-mentioned documents prepare different types of coatings on the surface of carbon fibers to resist oxidation of carbon fiber materials in high temperature environments. However, the modified carbon fiber materials in the above-mentioned documents have a high oxidation weight loss rate when subjected to a high temperature above 600°C. Summary of the invention
[0006] In order to overcome the shortcomings of the above-mentioned prior art, the purpose of the present invention is to provide a burst-type radiation-grown silicon nitride nanowire-modified carbon fiber material and a preparation method thereof, wherein the silicon nitride nanowires grow in a burst-type radiation manner around the carbon nanotube-modified carbon fiber, and the carbon fiber material grown with the above-mentioned silicon nitride nanowires has good antioxidant properties, reduces the weight loss rate of the carbon fiber material at high temperature, and prolongs the use time of the material under higher temperature oxidation conditions.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions: The present invention provides a burst radiation growth silicon nitride nanowire modified carbon fiber material, comprising silicon nitride nanowires and carbon nanotube modified carbon fibers; the silicon nitride nanowires burst radiation grow around the carbon nanotube modified carbon fibers; the silicon nitride nanowires cross-cover the surface of the carbon nanotube modified carbon fibers to form a network structure; the carbon nanotube modified carbon fibers have a double-layer pore structure around them, and the double-layer pore structure is the pores between the carbon nanotube modified carbon fibers and the silicon nitride nanowires and the micro-nano pores between the silicon nitride nanowires.
[0008] In one embodiment, the carbon nanotube-modified carbon fiber is prepared by in-situ growth of carbon nanotubes on the surface of the carbon fiber, wherein the carbon nanotubes serve as intermediates and the catalytic iron element at the tail end of the carbon nanotubes serves as the nucleation site for silicon nitride nanowires to form burst-radiatively grown silicon nitride nanowires.
[0009] The present invention also provides a method for preparing the burst radiation-grown silicon nitride nanowire modified carbon fiber material, comprising the following steps: Uniformly mixing ferrocene, ethylenediamine and anhydrous ethanol solution to obtain a mixed solution; Placing the cleaned carbon fiber in a chemical vapor deposition tube furnace, heating it to a first set temperature and then maintaining the temperature at the first set temperature, injecting the mixed solution into the chemical vapor deposition tube furnace, and then cooling and taking out the carbon nanotube-modified carbon fiber; Evenly mix polysilazane, ferrocene and xylene, stir evenly, naturally air-dry and then grind to obtain a powder sample; The carbon nanotube-modified carbon fiber is used as an upper cover, and the powder sample is placed in a U-shaped graphite box arranged below the carbon nanotube-modified carbon fiber, and the upper cover and the U-shaped graphite box are buckled to obtain the sample; The sample is placed in an atmosphere furnace, nitrogen is introduced, heated to a second set temperature, then kept at the second set temperature, and then cooled naturally to obtain a silicon nitride nanowire-modified carbon fiber material with a burst radiation growth morphology; Wherein, the gas flow rate of the nitrogen is 800~1200mL / min.
[0010] In one embodiment, the cleaning process is as follows: the carbon fiber is soaked in acetone and then dried for cleaning; the soaking time is 12 to 48 hours, and the drying time is 6 to 12 hours.
[0011] In one embodiment, the first set temperature is 800-850° C., and the insulation time at the first set temperature is 4-6 hours.
[0012] In one embodiment, the speed of injection of the mixed solution is 8-12 mL / h, and the time of injection of the mixed solution is 20-40 min.
[0013] In one embodiment, the mass ratio of ferrocene to anhydrous ethanol solution is 1:(60-65), and the mass ratio of ethylenediamine to anhydrous ethanol solution is 1:(15-20).
[0014] In one embodiment, the mass ratio of the polysilazane, ferrocene and xylene is 1:(9-10):(17-18).
[0015] In one embodiment, the amount of the powder sample in the U-shaped graphite box is 0.04-0.05 g / cm 2 .
[0016] In one embodiment, the second set temperature is 1430-1480° C., and the insulation time at the second set temperature is 2-3 hours.
[0017] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a burst radiation growth silicon nitride nanowire modified carbon fiber material, the silicon nitride nanowires are burst radiation growth around the carbon nanotube modified carbon fiber, the existence of the burst radiation growth silicon nitride nanowires makes a double-layer pore structure exist around the carbon nanotube modified carbon fiber, the pores between the carbon nanotube modified carbon fiber and the silicon nitride nanowires are relatively large, and there are micro-nano-level pores between the silicon nitride nanowires, the two pores increase air vibration, block heat transfer, increase the barrier between the carbon fiber material and oxygen, block the contact between oxygen and carbon fiber, and improve the material's anti-oxidation performance. The silicon nitride material itself is a ceramic material, and the silicon nitride nanowires form a cross-covered network structure on the surface of the carbon fiber. The cross-coverage of the silicon nitride nanowires blocks heat transfer and the contact between the carbon fiber and oxygen, thereby improving the anti-oxidation performance of the carbon fiber material and delaying the oxidation process of the carbon fiber material at a higher temperature.
[0018] Furthermore, carbon nanotubes were introduced as intermediates on the surface of carbon fibers to optimize the growth form of silicon nitride nanowires, thereby improving the antioxidant properties of carbon fiber materials. Carbon nanotubes were introduced and grown in situ on the surface of carbon fiber cloth to obtain carbon nanotube-modified carbon fibers. The carbon nanotubes not only enhanced the bonding force between the carbon fibers and the subsequent silicon nitride nanowires, but also provided the necessary catalytic sites for the growth of silicon nitride nanowires through the iron element at the tail end as a nucleation catalyst. Using the iron element at the tail end of the carbon nanotube as a catalyst, the silicon nitride nanowires showed a burst-like radiation growth morphology on the surface of the carbon nanotube-modified carbon fibers.
[0019] The present invention also provides a method for preparing the above-mentioned burst radiation growth silicon nitride nanowire modified carbon fiber material. Under the strong airflow, the silicon nitride nanowires grow in a burst radiation manner around the carbon nanotube modified carbon fiber. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a scanning electron microscope photograph of a silicon nitride nanowire carbon fiber monofilament with a burst radiation growth morphology prepared in Example 1 of the present invention; Figure 2 Another scanning electron microscope photograph of silicon nitride nanowire carbon fiber monofilament with burst radiation growth morphology prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope photograph of a silicon nitride nanowire-modified carbon fiber material without carbon nanotubes as an intermediate prepared in a comparative example of the present invention. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0022] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0023] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0024] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0025] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0026] The invention provides a burst radiation-grown silicon nitride nanowire modified carbon fiber material and a preparation method thereof.
[0027] The above-mentioned burst radiation growth silicon nitride nanowire modified carbon fiber material includes silicon nitride nanowires and carbon nanotube modified carbon fiber, and the silicon nitride nanowires are burst radiation growth around the carbon nanotube modified carbon fiber; wherein the silicon nitride nanowires cross-cover on the surface of the carbon nanotube modified carbon fiber to form a network structure; the carbon nanotube modified carbon fiber has a double-layer pore structure around it, and the double-layer pore structure is the pores between the carbon nanotube modified carbon fiber and the silicon nitride nanowires and the micro-nano pores between the silicon nitride nanowires. The carbon nanotube modified carbon fiber is prepared by in-situ growth of carbon nanotubes on the surface of carbon fiber, wherein the carbon nanotubes are used as intermediates, and the catalyst iron element at the tail end of the carbon nanotubes is used as the nucleation site of the silicon nitride nanowires to form burst radiation growth silicon nitride nanowires.
[0028] The inventive point of the present invention is that by introducing carbon nanotubes as intermediates, using the catalyst iron element at the tail end of the carbon nanotubes as the nucleation site of silicon nitride nanowires, and flushing with strong airflow, a silicon nitride nanowire-modified carbon fiber material with burst-type radiation growth is formed. Due to the special growth mode of silicon nitride nanowires, the material forms a double-layer pore structure around the carbon nanotube-modified carbon fiber, in which the pores include the pores between the carbon nanotube-modified carbon fiber and the silicon nitride nanowires and the micro-nano pores between the silicon nitride nanowires, which hinders heat transfer and thus reduces the temperature. In addition, the cross-coverage of silicon nitride nanowires reduces the contact between the carbon fiber and oxygen, thereby improving the antioxidant performance of the carbon fiber material.
[0029] The present invention also provides a method for preparing a burst radiation-grown silicon nitride nanowire-modified carbon fiber material, the steps of which are as follows: Step 1: uniformly mix ferrocene, ethylenediamine and anhydrous ethanol solution to obtain a mixed solution; wherein the mass ratio of ferrocene to the anhydrous ethanol solution is 1: (60-65), and the mass ratio of ethylenediamine to the anhydrous ethanol solution is 1: (15-20); By mixing ferrocene, ethylenediamine and anhydrous ethanol, a mixed solution containing a catalyst (ferrocene), a growth promoter (ethylenediamine) and a carbon source (anhydrous ethanol) is prepared for the subsequent vapor deposition process. Ferrocene, as a catalyst, can promote the growth of silicon nitride nanowires.
[0030] Step 2: Place the cleaned carbon fiber in a chemical vapor deposition tube furnace, heat it to a set temperature of 800-850°C, and then keep it at a set temperature of 800-850°C for 4-6 hours, inject the mixed solution into the chemical vapor deposition tube furnace, and then cool it to take out the carbon nanotube modified carbon fiber; the injection speed of the mixed solution is 8-12 mL / h, and the injection time is 20-40 min; At high temperature, the mixed solution is injected into a tubular furnace, so that the catalyst and carbon source in the mixed solution react on the surface of the carbon fiber to generate carbon nanotubes and provide nucleation sites for the subsequent growth of silicon nitride nanowires.
[0031] Step 3: uniformly mix polysilazane, ferrocene and xylene, stir evenly, naturally air-dry and then grind to obtain a powder sample; wherein the mass ratio of polysilazane, ferrocene and xylene is 1: (9-10): (17-18); By mixing polysilazane, ferrocene and xylene, a powder sample containing a silicon nitride precursor (polysilazane) and a catalyst (ferrocene) was prepared for the subsequent growth of silicon nitride nanowires. Polysilazane can be converted into silicon nitride at high temperatures, and ferrocene, as a catalyst, promotes the growth of silicon nitride nanowires. The preparation of the powder sample ensures the uniform mixing of the silicon nitride precursor and the catalyst, which is conducive to the uniform growth of subsequent silicon nitride nanowires.
[0032] Step 4: Use carbon nanotube modified carbon fiber as the upper cover and add 0.04~0.05 g / cm 2 The powder sample is placed in a U-shaped graphite box arranged below the carbon nanotube-modified carbon fiber, and the upper cover and the U-shaped graphite box are buckled to obtain the sample; The carbon nanotube-modified carbon fiber is used as the upper cover of the U-shaped graphite box, and the powder sample is placed in the lower box to grow silicon nitride nanowires at high temperature. The design of the U-shaped graphite box allows the carbon nanotube-modified carbon fiber and the powder sample to be in close contact, which is conducive to the uniform growth of silicon nitride nanowires on the surface of the carbon fiber. At the same time, the graphite box has good thermal conductivity, which ensures the uniformity of the heating process.
[0033] Step 6: Place the sample in an atmosphere furnace, introduce nitrogen at an ultra-high gas flow rate of 800~1200mL / min, heat to a set temperature of 1430~1480℃, keep it at the set temperature for 2~3h, and then cool it naturally to obtain a silicon nitride nanowire-modified carbon fiber material with a burst radiation growth morphology.
[0034] Under nitrogen protection, the sample was subjected to high-temperature heat treatment to convert the polysilazane in the powder sample into silicon nitride nanowires, which were then flushed by strong airflow to form a burst-like radiation growth morphology on the carbon fiber surface. High-temperature heat treatment promoted the growth of silicon nitride nanowires, while nitrogen protection prevented the carbon fiber from oxidizing at high temperatures.
[0035] The silicon nitride nanowire-modified carbon fiber material with a burst radiation growth morphology prepared by the above preparation method improves the oxidation resistance of the carbon fiber, and the formation of a double-layer pore structure further improves the thermal insulation performance of the material and reduces gas permeability.
[0036] Furthermore, the carbon fiber cloth is soaked in acetone and then dried for cleaning before use; acetone soaking can remove oil, impurities and loose fibers on the surface of the carbon fiber, improve the cleanliness and activity of the carbon fiber surface, and facilitate the subsequent in-situ growth of carbon nanotubes. Drying is to remove acetone residues to avoid adverse effects on subsequent steps, improve the bonding strength between the carbon fiber and the subsequent coating, and ensure the uniformity and density of the coating.
[0037] The specific preparation method is as follows: (1) Soak the carbon fiber in acetone for 12 to 48 hours and then dry it in an oven for 6 to 12 hours to obtain cleaned carbon fiber.
[0038] (2) Evenly mixing ferrocene, ethylenediamine and anhydrous ethanol solution, wherein the mass ratio of ferrocene to anhydrous ethanol is 1:60-1:65, and the mass ratio of ethylenediamine to anhydrous ethanol is 1:15-1:20, to obtain a mixed solution.
[0039] (3) The cleaned carbon fiber is placed in a chemical vapor deposition tube furnace, heated to 800-850°C and kept warm for 4-6 hours, and the mixed solution is injected into the tube furnace at a rate of 8-12 mL / h for 20-40 minutes until the furnace tube is cooled and the sample is taken out to obtain carbon nanotube-modified carbon fiber.
[0040] (4) Evenly mix polysilazane, ferrocene, and xylene, wherein the mass ratio of ferrocene to polysilazane is 1:9-1:10, and the mass ratio of ferrocene to xylene is 1:17-1:18. Stir evenly, then naturally air-dry and grind to obtain a powder sample.
[0041] (5) The carbon nanotube-modified carbon fiber is used as the upper cover, and the lower part of the upper cover is a U-shaped graphite box, and 0.04~0.05g / cm 2 The powder sample is placed in a U-shaped graphite box, and the upper cover and the lower box are buckled together to obtain the sample.
[0042] (6) The sample was placed in a box-type atmosphere furnace, nitrogen was introduced at a flow rate of 800-1200 mL / min, heated to 1430°C-1480°C, kept at this temperature for 2-3 h, and then naturally cooled to obtain a silicon nitride nanowire-modified carbon fiber material with a burst radiation growth morphology.
[0043] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0044] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0045] Example 1 (1) Soak the carbon fiber cloth in acetone for 24 hours and then dry it in an oven for 6 hours to obtain cleaned carbon fiber.
[0046] (2) Evenly mixing ferrocene, ethylenediamine and anhydrous ethanol solution, wherein the mass ratio of ferrocene to anhydrous ethanol is 1:60, and the mass ratio of ethylenediamine to anhydrous ethanol is 1:15, to obtain a mixed solution.
[0047] (3) The cleaned carbon fiber was placed in a chemical vapor deposition tube furnace, heated to 800°C and kept warm for 4 hours, and the mixed solution was injected into the tube furnace at a rate of 8 mL / h for 20 minutes until the furnace tube was cooled and the sample was taken out to obtain carbon nanotube-modified carbon fiber.
[0048] (4) Evenly mix polysilazane, ferrocene, and xylene, wherein the mass ratio of ferrocene to polysilazane is 1:9, and the mass ratio of ferrocene to xylene is 1:17. After stirring evenly, naturally air-dry and grind to obtain a powder sample.
[0049] (5) The carbon nanotube-modified carbon fiber is used as the upper cover, and the lower part of the upper cover is a U-shaped graphite box, and 0.04 g / cm 2 The powder sample is placed in a U-shaped graphite box, and the upper cover and the lower box are buckled together to obtain the sample.
[0050] (6) The sample was placed in a box-type atmosphere furnace, heated to 1430°C in a nitrogen atmosphere at a flow rate of 800 mL / min, kept at this temperature for 3 h, and then naturally cooled to obtain a carbon fiber material modified with silicon nitride nanowires having burst radiation growth.
[0051] Example 1 prepared a carbon fiber material with burst radiation growth of silicon nitride nanowires, whose oxidation weight loss rate at 400°C for 1 hour was 17.5%, the oxidation weight loss rate at 500°C for 1 hour was 19.2%, the oxidation weight loss rate at 600°C for 1 hour was 18.7%, and the oxidation weight loss rate at 700°C for 30 minutes was 45.31%.
[0052] Example 2 (1) After soaking the carbon fiber cloth in acetone for 48 hours, the carbon fiber cloth was dried in an oven for 12 hours to obtain cleaned carbon fiber.
[0053] (2) Evenly mixing ferrocene, ethylenediamine and anhydrous ethanol solution, wherein the mass ratio of ferrocene to anhydrous ethanol is 1:65, and the mass ratio of ethylenediamine to anhydrous ethanol is 1:18, to obtain a mixed solution B.
[0054] (3) The cleaned carbon fiber was placed in a chemical vapor deposition tube furnace, heated to 850°C and kept warm for 6 hours, and the mixed solution was injected into the tube furnace at a rate of 12 mL / h for 40 minutes until the furnace tube was cooled and the sample was taken out to obtain carbon nanotube-modified carbon fiber.
[0055] (4) Evenly mix polysilazane, ferrocene, and xylene, wherein the mass ratio of ferrocene to polysilazane is 1:10, and the mass ratio of ferrocene to xylene is 1:18, stir evenly, and then naturally air-dry and grind to obtain a powder sample.
[0056] (5) The carbon nanotube-modified carbon fiber is used as the upper cover, and the lower part of the upper cover is a U-shaped graphite box, and 0.0485 g / cm 2 The powder sample is placed in a U-shaped graphite box, and the upper cover and the lower box are buckled together to obtain the sample.
[0057] (6) The sample was placed in a box-type atmosphere furnace, heated to 1480°C in a nitrogen atmosphere at a flow rate of 1000 mL / min, kept at this temperature for 2 h, and then naturally cooled to obtain a carbon fiber material modified with silicon nitride nanowires having burst radiation growth.
[0058] Example 2 prepared a carbon fiber material with burst radiation-grown silicon nitride nanowires, whose oxidation weight loss rate at 400°C for 1 h was 16.9%, the oxidation weight loss rate at 500°C for 1 h was 20.79%, the oxidation weight loss rate at 600°C for 1 h was 21.1%, and the oxidation weight loss rate at 700°C for 1 h was 49.23%.
[0059] Example 3 (1) Soak the carbon fiber cloth in acetone for 24 hours and then dry it in an oven for 9 hours to obtain cleaned carbon fiber.
[0060] (2) Evenly mixing ferrocene, ethylenediamine and anhydrous ethanol solution, wherein the mass ratio of ferrocene to anhydrous ethanol is 1:62, and the mass ratio of ethylenediamine to anhydrous ethanol is 1:17, to obtain a mixed solution.
[0061] (3) The cleaned carbon fiber was placed in a chemical vapor deposition tube furnace, heated to 830°C and kept warm for 5 hours, and the mixed solution was injected into the tube furnace at a rate of 10 mL / h for 30 minutes until the furnace tube was cooled and the sample was taken out to obtain a sample.
[0062] (4) Evenly mix polysilazane, ferrocene, and xylene, wherein the mass ratio of ferrocene to polysilazane is 1:9.5, and the mass ratio of ferrocene to xylene is 1:17.5. After stirring evenly, naturally air-dry and grind to obtain a powder sample.
[0063] (5) The carbon nanotube-modified carbon fiber is used as the upper cover, and the lower part of the upper cover is a U-shaped graphite box, and 0.05 g / cm 2 The powder sample is placed in a U-shaped graphite box, and the upper cover and the lower box are buckled together to obtain the sample.
[0064] (6) The sample was placed in a box-type atmosphere furnace, heated to 1450°C in a nitrogen atmosphere at a flow rate of 1200 mL / min, kept at this temperature for 3 h, and then naturally cooled to obtain a carbon fiber material modified with silicon nitride nanowires having burst radiation growth.
[0065] Example 3 prepared a carbon fiber material with burst radiation growth of silicon nitride nanowires, whose oxidation weight loss rate at 400°C for 1 hour was 17.79%, the oxidation weight loss rate at 500°C for 1 hour was 18.6%, the oxidation weight loss rate at 600°C for 1 hour was 19.25%, and the oxidation weight loss rate at 700°C for 30 minutes was 43.56%.
[0066] Example 4 (1) Soak the carbon fiber cloth in acetone for 24 hours and then dry it in an oven for 12 hours to obtain cleaned carbon fiber.
[0067] (2) Evenly mixing ferrocene, ethylenediamine and anhydrous ethanol solution, wherein the mass ratio of ferrocene to anhydrous ethanol is 1:62, and the mass ratio of ethylenediamine to anhydrous ethanol is 1:20, to obtain a mixed solution.
[0068] (3) The cleaned carbon fiber was placed in a chemical vapor deposition tube furnace, heated to 850°C and kept warm for 6 hours, and the mixed solution was injected into the tube furnace at a rate of 12 mL / h for 40 minutes until the furnace tube was cooled and the sample was taken out to obtain carbon nanotube-modified carbon fiber.
[0069] (4) Evenly mix polysilazane, ferrocene, and xylene, wherein the mass ratio of ferrocene to polysilazane is 1:9.6, and the mass ratio of ferrocene to xylene is 1:20. After stirring evenly, naturally air-dry and grind to obtain a powder sample.
[0070] (5) The carbon nanotube-modified carbon fiber is used as the upper cover, and the lower part of the upper cover is a U-shaped graphite box, and 0.0435 g / cm 2 The powder sample is placed in a U-shaped graphite box, and the upper cover and the lower box are buckled together to obtain the sample.
[0071] (6) The sample was placed in a box-type atmosphere furnace, heated to 1460°C in a nitrogen atmosphere at a flow rate of 900 mL / min, kept at this temperature for 3 h, and then naturally cooled to obtain a carbon fiber material modified with silicon nitride nanowires having burst radiation growth.
[0072] Example 4 prepared a carbon fiber material with burst radiation growth of silicon nitride nanowires, whose oxidation weight loss rate at 400°C for 1 h was 17.1%, the oxidation weight loss rate at 500°C for 1 h was 21.36%, the oxidation weight loss rate at 600°C for 1 h was 21.79%, and the oxidation weight loss rate at 700°C for 30 min was 44.74%.
[0073] Comparative Example (1) Soak the carbon fiber cloth in acetone for 24 hours and then dry it in an oven for 9 hours to obtain cleaned carbon fiber.
[0074] (2) Polysilazane, ferrocene and xylene are uniformly mixed, wherein the mass ratio of ferrocene to polysilazane is 1:9.2, and the mass ratio of ferrocene to xylene is 1:18. After uniform mixing, the mixture is naturally air-dried and ground to obtain a powder sample.
[0075] (3) Make a U-shaped graphite box with the upper and lower parts buckled. Use the cleaned carbon fiber as the upper cover of the U-shaped graphite box. The lower part of the upper cover is the U-shaped graphite box. Place about 0.0440 g / cm 2 of powder sample to obtain a sample.
[0076] (4) The sample was placed in a box-type atmosphere furnace, heated to 1450°C at a nitrogen flow rate of 1200 mL / min, kept at this temperature for 3 h, and then naturally cooled to obtain clustered flower-shaped silicon nitride nanowires.
[0077] like Figure 3 As shown, the comparative example did not fully follow the preparation process, and failed to prepare silicon nitride nanowires with burst radiation growth on the carbon fiber surface. The comparative example obtained silicon nitride nanowires with ordinary morphology.
[0078] from Figure 1 It can be seen that the burst radiation-grown silicon nitride nanowire-modified carbon fiber material has two pore structures, one is the pores around the carbon nanotube-modified carbon fiber, and the other is the micro-nano pores between the silicon nitride nanowires. Figure 2 It can be seen that the silicon nitride nanowires in the silicon nitride nanowire-modified carbon fiber material prepared using carbon nanotubes as intermediates under strong airflow scouring show obvious burst-like radiation.
[0079] Introducing carbon nanotubes as intermediates on the surface of carbon fiber, optimizing the growth form of silicon nitride nanowires, and improving the oxidation resistance of carbon fiber materials. The modified carbon fiber obtained by the method proposed in the present invention has an oxidation weight loss rate of 18.7% at 600°C. In order to verify the improvement of the antioxidant effect of silicon nitride nanowires grown by burst radiation on carbon fiber materials, the modified carbon fiber prepared in Example 1 of the present invention and the unmodified carbon fiber were subjected to oxidation weight loss tests, and were placed in oxidation furnaces at 400°C, 500°C, 600°C and 700°C, respectively, and their initial weight and the weight of the sample after oxidation were measured, and the oxidation weight loss rate of the material was calculated. The results are shown in Table 1.
[0080] Table 1 Oxidation weight loss test table
[0081] By comparing the oxidation weight loss rates of Example 1 and pure carbon cloth, it can be seen that the weight loss rate of Example 1 is less than that of pure carbon cloth at the same oxidation temperature and oxidation time, that is, the antioxidant capacity of Example 1 is stronger than that of pure carbon cloth, and the enhancement effect is significantly higher than that of the aforementioned literature. It is proved that the burst radiation-grown silicon nitride nanowires can significantly optimize the antioxidant capacity of carbon fibers. At the same time, by comparing Example 1 and the comparative example, it can be seen that without using carbon nanotubes as intermediates, it is impossible to prepare silicon nitride nanowire-modified carbon fiber materials with burst radiation-grown morphology.
[0082] The reason for obtaining such excellent performance is that the present invention includes silicon nitride nanowires and carbon nanotube modified carbon fibers, and the silicon nitride nanowires grow in burst radiation around the carbon nanotube modified carbon fibers. The carbon nanotubes are grown in situ on the surface of the carbon fibers to obtain the carbon nanotube modified carbon fibers. By introducing carbon nanotubes as intermediates, the catalyst iron element at the tail end of the carbon nanotubes is used as the nucleation site (nucleation catalyst) of the silicon nitride nanowires, and by strong airflow flushing, a silicon nitride nanowire modified carbon fiber material with a burst radiation growth morphology is formed. In the silicon nitride nanowire modified carbon fiber material, the silicon nitride nanowires grow in burst radiation around the carbon nanotube modified carbon fiber. Due to the special growth mode of the silicon nitride nanowires, a double-layer pore structure with two kinds of pores is formed around the carbon nanotube modified carbon fiber, wherein the pores include the pores between the carbon nanotube modified carbon fiber and the silicon nitride nanowires and the micro-nano pores between the silicon nitride nanowires. The existence of the two kinds of pores increases air vibration, hinders heat transfer, increases the barrier between the carbon fiber material and oxygen, and blocks the contact between oxygen and the carbon fiber, thereby reducing the temperature. In addition, the silicon nitride material itself is a ceramic material, and the cross-coverage of the silicon nitride nanowires on the surface of the carbon nanotube modified carbon fiber forms a network structure that hinders heat transfer and the contact between the carbon nanotube modified carbon fiber and oxygen, delays the oxidation process of the carbon fiber material at higher temperatures, thereby improving the anti-oxidation performance of the carbon fiber material.
[0083] The minimum oxidation weight loss rate of carbon fiber materials reported in existing literature at 600°C is 40%, while the minimum oxidation weight loss rate of the modified carbon fiber obtained by the method proposed in the present invention at 600°C is 18.7%. In summary, the results of the present invention are significantly lower than the oxidation weight loss rate values reported in the literature.
[0084] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A burst radiation-grown silicon nitride nanowire modified carbon fiber material, characterized in that: Including silicon nitride nanowires and carbon nanotube modified carbon fibers; The silicon nitride nanowires grow in a bursting radiation manner around the carbon nanotube-modified carbon fibers; the silicon nitride nanowires cross-cover the surface of the carbon nanotube-modified carbon fibers to form a network structure; The carbon nanotube modified carbon fiber has a double-layer pore structure around it, and the double-layer pore structure is the pores between the carbon nanotube modified carbon fiber and the silicon nitride nanowires and the micro-nano pores between the silicon nitride nanowires.
2. The burst radiation grown silicon nitride nanowire modified carbon fiber material according to claim 1, characterized in that: The carbon nanotube modified carbon fiber is prepared by in-situ growth of carbon nanotubes on the surface of carbon fiber. The carbon nanotubes are used as intermediates, and the catalyst iron element at the tail end of the carbon nanotubes is used as the nucleation site of silicon nitride nanowires to form burst-type radiation-grown silicon nitride nanowires.
3. A method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to any one of claims 1 to 2, characterized in that: The following steps are involved: Uniformly mixing ferrocene, ethylenediamine and anhydrous ethanol solution to obtain a mixed solution; Placing the cleaned carbon fiber in a chemical vapor deposition tube furnace, heating it to a first set temperature and then maintaining the temperature at the first set temperature, injecting the mixed solution into the chemical vapor deposition tube furnace, and then cooling and taking out the carbon nanotube-modified carbon fiber; Evenly mix polysilazane, ferrocene and xylene, stir evenly, naturally air-dry and then grind to obtain a powder sample; The carbon nanotube-modified carbon fiber is used as an upper cover, and the powder sample is placed in a U-shaped graphite box arranged below the carbon nanotube-modified carbon fiber, and the upper cover and the U-shaped graphite box are buckled to obtain the sample; The sample is placed in an atmosphere furnace, nitrogen is introduced, heated to a second set temperature, then kept at the second set temperature, and then cooled naturally to obtain a silicon nitride nanowire-modified carbon fiber material with a burst radiation growth morphology; Wherein, the gas flow rate of the nitrogen is 800~1200mL / min.
4. The method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The cleaning process is as follows: the carbon fiber is soaked in acetone and then dried for cleaning; the soaking time is 12 to 48 hours, and the drying time is 6 to 12 hours.
5. The method for preparing the carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The first set temperature is 800-850° C., and the insulation time at the first set temperature is 4-6 hours.
6. The method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The speed of the mixed solution injection is 8-12 mL / h, and the time of the mixed solution injection is 20-40 min.
7. The method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The mass ratio of the ferrocene to the anhydrous ethanol solution is 1:(60-65), and the mass ratio of the ethylenediamine to the anhydrous ethanol solution is 1:(15-20).
8. The method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The mass ratio of the polysilazane, ferrocene and xylene is 1:(9-10):(17-18).
9. The method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The amount of powder sample in the U-shaped graphite box is 0.04-0.05 g / cm 2 .
10. The method for preparing a carbon fiber material modified by burst radiation growth of silicon nitride nanowires according to claim 3, characterized in that: The second set temperature is 1430-1480° C., and the insulation time at the second set temperature is 2-3 hours.
Citation Information
Cited By
Nanometer bamboo joint-nanowire two-component composite film and preparation method thereof
CN118479889A
A nano-bamboo joint-nanowire dual-component composite film and a preparation method thereof
CN118479889B